Math, asked by geetarawat1517, 4 months ago

3/√3+1=a+b√3
pls answer jaldi dena​

Answers

Answered by himanshisheoran4
1

Step-by-step explanation:

may be helpful ❤

hope it completely helps you....

Attachments:
Answered by Anonymous
1

 \frac{ \sqrt{3 - 1} }{ \sqrt{3 + 1} }

 =  >  \frac{ \sqrt{3 - 1} }{ \sqrt{3 - 1} }  \times  \frac{ \sqrt{3 - 1} }{ \sqrt{3 - 1} }

 =  >  \frac{( \sqrt{3 - 1) ^{2} } }{( \sqrt{3) ^{2} -  {1}^{2}  } }

 =  >  \frac{3 - 2 \times  \sqrt{3 \times 1 + 1} }{3 - 1}

 =  >  \frac{4 -  \sqrt[2]{3} }{2}

 =  > 2 -  \sqrt{3}

 =  > 2  + ( - 1) \sqrt{3}

 =  > a - b \sqrt{3}

Hence, a= 2 and b= -1

Similar questions